Modelling of Production Relations in the Lithuanian Economy - Filatovaitė, Daina; Bratčikovienė, Nomeda (Lithuanian Journal of Statistics, 2015)
This paper presents a method for the analysis of price index changes in each branch of thecountry’s economy given changes in production factors. Cobb–Douglas production functions were evaluated foreach sector separately enabling the forecasting of production quantities. The country’s total production functionwas estimated using conditional regression. Later, an inter-branch balance problem of price and productionvolume relationship evaluation was solved using a Lithuanian input–output table. Finally, combining the estimatedproduction functions and estimated price–output relationship, Lithuanian economy-relevant scenarios ofre-emigration and retail chain Lidl investment were analysed.
Keywords: Cobb–Douglas production function; price forecast; input-output table; scenarios of the Lithuanian economy